Is the Central Bank Gone Mad: Executive Compensation with Reference to the Nepalese Banking Industry - Bhatta, Kiran Prasad (Banking Journal, 2012)
DOI: http://dx.doi.org/10.3126/bj.v2i2.6623Banking Journal, Volume 2 (Issue 2) 64-96